The love fix : a novel - Shalvis, Jill (Shalvis, Jill. Sunrise Cove novels, 2025)
"Lexi Clark's life is falling apart around her, so when she's summoned home to Sunrise Cove, the last thing she wants to do is face all the complications she left behind. Her past, her stepsister Ashley, and especially her infuriatingly gorgeous childhood nemesis-turned-crush Heath Bowman. Yep, Lexi's pretty sure being home again just might kill her. She's an overachieving art appraiser who doesn't believe in trust, love, or Happily Ever Afters. Free spirit Ashley, on the other hand, is so full of life it hurts to look at her. But Lexi can't refuse Ashley's plea to honor their late mother's final wish to make amends with the people she'd wronged. So, on behalf of her estranged mother's estate--and with Heath in tow as the executor--Lexi embarks on a road trip to repay all the people her gambling addicted mother owed money to. Complicating everything are the feelings that well up for Lexi: for her mom, for Ashley, and most of all, for Heath. And for the record, she doesn't like it, or the way he has of scaling the walls she's built around her heart. The road trip shenanigans that ensue are both funny and heartbreaking, but Lexi finds something shocking along the way. Acceptance. Family. And unbelievably--if you ask Lexi anyway--love"--